2007
DOI: 10.1080/00015458.2007.11680146
|View full text |Cite
|
Sign up to set email alerts
|

The Right Method for Midline Laparotomy: What is the Best Choice for Wound Healing ?

Abstract: HS causes less inflammatory reaction and necrosis than diathermy, but more necrosis than CS. Fascia incisions with CS gains tensile strength faster than in other groups. HS appears to cause less tissue injury than diathermy and also has comparable results for wound healing. Further clinical studies on the impact of HS in fascia incisions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…However, it is still infrequently used for making skin incisions. The reluctance in the use of skin incision is due to the fear that electro surgical instruments create increased amounts of necrotic tissue within the wound which may increase the chances of wound infection leading to delayed wound healing and excessive scarring ( 2 , 8 - 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still infrequently used for making skin incisions. The reluctance in the use of skin incision is due to the fear that electro surgical instruments create increased amounts of necrotic tissue within the wound which may increase the chances of wound infection leading to delayed wound healing and excessive scarring ( 2 , 8 - 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, many studies have been conducted on both methods of skin incision, which showed less operating time, diminished loss of blood, and reduced early pain and fewer requirements of analgesic drugs after surgery using the diathermy method of skin incision when compared to scalpel incision ( 2 ). In one experimental study, conducted on rats, it was shown that wound incisions made with a cold scalpel had more rapid tensile strengths as compared to diathermy or harmonic scalpels ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The entity of tissue damage and the nature of the energy and the time of its application on tissues could impair the regeneration events and growth process; in particular thermal energy, as diathermy, used to incision and tissue dissection seems to be associated with more cellular damage and soft tissue devastation. Have been shown faster operating times, reduced blood loss and early post-operative pain and lower analgesia using diathermy for skin incision if compared with cold blade [18,19], but this is a “speedy procedure” for a linear and regular cutting with short and “constant moving” energy application and quickly heat dispersion and rapid return of cut tissues to normal body temperature. In this use the damage and the heat burn is limited to the section line and short in time, with no involvement and spreading to the close tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with co-morbids conditions like diabetes mellitus and hypertension were the included in this study to observe that weather the diseases have an effect on wound healing, but no significant difference was found; complication rates were similar as in other studies that had patients without co-morbids. 8,9 The most compelling reason for the routine use of cutting diathermy for skin incisions, therefore, is removal of the scalpel from the operating theatre and elimination of an important cause of injury. We did not find any difference in the rate of wound complications between cutting diathermy and scalpel in our study.…”
Section: Discussionmentioning
confidence: 99%